Australian Directors Define Corporate Governance - McCabe, Margaret (The International Management Development Association, 2005)
Increasingly there is a call for refining and defining what is understood when using the term corporate governance. The research reported on here provides a definition constructed from the language used by directors of public listed companies in Australia. Analysis of the definition reveals a departure from the traditional language that was reflective of agency theory and reliance by directors on language that is consistent with the underlying principles of stakeholder theory. Furthermore the provision for multiple and varied stakeholders in a constantly changing environment aligns with the principles of complex adaptive systems theory .